2010
DOI: 10.1074/jbc.m109.094557
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Consequences of the ACVR1R206H Mutation of Fibrodysplasia Ossificans Progressiva

Abstract: Fibrodysplasia ossificans progressiva (FOP), a rare genetic and catastrophic disorder characterized by progressive heterotopic ossification, is caused by a point mutation, c.617G>A; p.R206H, in the activin A receptor type 1 (ACVR1) gene, one of the bone morphogenetic protein type I receptors (BMPR-Is). Although altered BMP signaling has been suggested to explain the pathogenesis, the molecular consequences of this mutation are still elusive. Here we studied the impact of ACVR1 R206H mutation on BMP signaling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
99
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 66 publications
11
99
0
Order By: Relevance
“…The mechanisms by which ALK2(R206H) transfection induces MMP-10 levels in C2C12 cells are still unknown in the present study. BMP family proteins, including BMP-2, 4, 6 and 7, affect cells through ALK2, and the ALK2 (R206H) mutation mildly activates BMP signaling, as previously reported [4]. Although the most crucial ligand of ALK2 for the pathogenesis of FOP have not been determined yet, our preliminary study revealed that exogenous BMP-2 addition did not induce the levels of MMP-10 mRNA in C2C12 cells (data not shown).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The mechanisms by which ALK2(R206H) transfection induces MMP-10 levels in C2C12 cells are still unknown in the present study. BMP family proteins, including BMP-2, 4, 6 and 7, affect cells through ALK2, and the ALK2 (R206H) mutation mildly activates BMP signaling, as previously reported [4]. Although the most crucial ligand of ALK2 for the pathogenesis of FOP have not been determined yet, our preliminary study revealed that exogenous BMP-2 addition did not induce the levels of MMP-10 mRNA in C2C12 cells (data not shown).…”
Section: Discussionsupporting
confidence: 49%
“…The previous studies showed that ALK2 (R206H) constitutively activates BMP signaling through Smad1/5/8, thereby contributing to the ectopic bone formation in FOP, a disease characterized by marked heterotopic ossification in muscle tissues [1][2][3][4]. We therefore performed a comparative DNA microarray analysis between empty vector-and ALK2 (R206H)-stably transfected mouse myoblastic C2C12 cells to anism of MMP-10 effects on the differentiation of myoblastic cells into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…ACVR1 mutations in atypical FOP patients have been found also in other amino acids of the GS domain or protein kinase domain (11,12). Regardless of the mutation site, mutated ACVR1 (FOP-ACVR1) has been shown to activate BMP signaling without exogenous BMP ligands (constitutive activity) and transmit much stronger BMP signaling after ligand stimulation (hyperactivity) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…To reveal the molecular nature of how FOP-ACVR1 activates BMP signaling, cells overexpressing FOP-ACVR1 (12)(13)(14)(15)(16)(17)(18)(19)(20), mouse embryonic fibroblasts derived from Alk2 R206H/+ mice (21,22), and cells from FOP patients, such as stem cells from human exfoliated deciduous teeth (23), FOP patient-derived induced pluripotent stem cells (FOP-iPSCs) (24,25) and induced mesenchymal stromal cells (iMSCs) from FOP-iPSCs (FOP-iMSCs) (26) have been used as models. Among these cells, Alk2 R206H/+ mouse embryonic fibroblasts and FOP-iMSCs are preferred because of their accessibility and expression level of FOP-ACVR1 using an endogenous promoter.…”
mentioning
confidence: 99%
“…They suggested that miR-148a is an important mediator of ACVR1, thus offering a new potential target for the development of therapeutic agents against FOP (Song et al, 2012). According to Song et al (2010), the p.R206H mutant showed a decreased binding affinity for FKBP1A/FKBP12, a known safeguard molecule against the leakage of transforming growth factor (TGF)-beta or BMP signaling. The decreased binding affinity of FKBP1A to the mutant p.R206H ACVR1 resulted in leaky activation of the BMP signal, and moreover, it decreased steady-state p.R206H ACVR1 protein levels.…”
Section: How the Acvr1-bmps Signaling Is Associated With Fop?mentioning
confidence: 99%